Relationship Between Parents Parenting With Teenage Premarital Sexual Behavior - Santika Nurjanah; Ariyati Mandiri; Didah Didah; Neneng Martini; Dini Saraswati Handayani (Journal of Nursing Care, 2021)
Adolescence is a period of transition and development in sexuality. The development of adolescent sexuality can be seen from adolescent sexual behavior. Through an interview, adolescents who are given authoritative and authoritarian [arenting have a low risk of sexual behavior because their parents restrict their children from doing everything. The purpose of study was to determine the relationship between parenting style and premartial sexual behavior among adolescents in cisempur. The Sampling technique used simple random sampling with 86 teenage respondents and parents as respondents. Data collection using questionnaires. The results of the research on the parenting pattern of all respondents obtained as many as 93%, as many as authoritative 2.3%, as many as Authoritarian and as much as 4.7% Permissive. The results of the study on premarital sexual behavior were 64% low risk and 36% not at risk with the results of the correlation test value > 0.05, thus most parents have authoritative parenting, most adolescents have low risk in premarital sexual behavior The conclusion of the study there is no relationship between parenting patterns and premarital sexual behavior in adolescents. Suggestions related to the results need further research to determine other factors of adolescents engaging in premarital sexual behavior.Keywords: adolescents, parenting, premarital sexual behavior